The Internal Structure Of Paricutin And Tancítaro Volcanos, Mexico, From Rock Density Distributions - Alvarez, R.; Camacho, Miguel; Rivera-Calderón, Elizabeth (Transactions on Engineering and Computing Sciences, 2024)
Located in the Tarascan plateau, western Mexico, Paricutín volcano is the youngest monogenetic volcano in the country; it is located within 6 km of the only stratovolcano in that region: Tancítaro volcano. The objective is to define the location of Paricutín’s magma chamber and the magma conduits constituting its plumbing system. For that purpose, we use a high-resolution, satellite-derived gravity data set to obtain 3D density inversions at two spatial resolutions of 500 and 250 m. Results from the 500 m resolution led us to suspect that a branch of Tancítaro’s magma chamber fed Paricutín’s eruption; however, at this resolution, we could not find a magmatic path linking them. Results at the higher resolution (250 m) unveiled a channel within a high-density region, in which a vertical, low-density channel is located under Paricutín extending down to 5 km depth, including a region at sea level, that we associate with a small magma chamber owing to its shape and lower density. The volume identified as the magma chamber of Tancítaro volcano is enclosed by a formation of high-density material that appears to have been intruded prior to the emplacement of the Tancítaro magma chamber; its nature and composition cannot be determined with the available information.